Dialek Arab Fusha dan Arab Amiyah Yaman dalam Aspek Kosakata, Fonologi, dan Morfologi - Munazzalurrohmi, Muhammad; Mubarok, Khusnul; Akbar, Syawal Rizki (Universitas Negeri Jakarta, 2025)
Arabic is one of the branches of the Semitic language family that still exists and continues to develop rapidly today. One indicator of this development is the presence of various dialects within the Arabic language. These dialects have spread across regions, from West Asia (the Middle East) to North Africa. As a result, what is known as fuṣḥá Arabic and ‘āmiyah Arabic emerged. Fuṣḥá is the standard form of the language, while ‘āmiyah refers to regional dialects. This research discusses the differences between Fuṣḥá Arabic and Yemeni Arabic. The study was conducted due to the lack of research explicitly addressing the distinctions between these two forms. This research explores how Yemeni Arabic is used in daily life and how it differs from Fuṣḥá Arabic. The method used is a literature review with a qualitative descriptive approach. The findings reveal several key differences between Fuṣḥá Arabic and Yemeni Arabic, which are categorized into three main aspects: vocabulary, phonology, and stylistics. These aspects are analyzed in detail, highlighting the linguistic distinctions between the two varieties.